Tariffs, Retaliation, and the Elasticity of Demand for Imports - Gorman, W. M. (Review of Economic Studies, 1958)
Journal Article Tariffs, Retaliation, and the Elasticity of Demand for Imports Get access W. M. Gorman W. M. Gorman Birmingham and Ames, Iowa Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 3, June 1958, Pages 133–162, https://doi.org/10.2307/2295983 Published: 01 June 1958